An ultralow power nanosensor array for selective detection of air pollutants. (10th October 2019) - Prajapati, Chandra Shekhar; Benedict, Samatha; Bhat, Navakanta
Abstract: Semiconducting metal oxide gas sensors typically operate at a high temperature and consume hundreds of milliwatts of power. Therefore there is great demand for the development of a low-power gas-sensing technology that can sensitively and selectively detect the gas analytes present in the atmosphere. We report an ultralow-power nanosensor array platform, integrated with an independently controlled nanoheater of size 4 μ m × 100 nm, which consumes ∼1.8 mW power when operated continuously at 300 °C. The heaters exhibit a fast thermal response time of less than 1 μ s, and can be utilized to operate in duty cycle mode, leading to power saving. The active area of the nanosensor is 1 μ m × 200 nm, defined by sensing electrodes with a nanogap of ∼200nm, leading to small form factor. As a proof of concept, each of the sensing elements in the array is functionalized with different sensing materials to demonstrate a low-power, sensitive and selective multiplexed gas-sensing technology for the simultaneous detection of CO (∼93.2% for 3 ppm at 300 °C), CO2 (∼76.3% for 1000 ppm at 265 °C), NO2 (∼2301% for 3 ppm at 150 °C) and SO2 (∼94% for 3 ppm at 265 °C). The technology described here uses scalable crossbar architecture for sensor elements, thus enabling the integration of additional sensing materials and making it customizable for specific applications.